Pengaruh Penggunaan Media Blog Terhadap Minat Belajar Siswa pada Keterampilan Menulis Pengalaman Pribadi - Rida, Andi; Bahri, Aliem; Paida, Andi (Fakultas Sastra Universitas Muslim Indonesia, 2024)
The purpose of this research is to determine the use of blog media on learning interest in writing skills, and personal experiences of class V students at SDN 179 Tanah Beru, Bulukumba Regency, in terms of the use of student interest response questionnaires. The type of research used is pre-experimental research. The research design used is a one-shot case study, namely experimental research carried out by demonstrating the strength of measurement and scientific value of a research design. The experimental subjects in this research were 19 students as a trial class to apply the use of blog media. The data collection technique used is a questionnaire technique of student learning interests or student responses. The research results show that from the results of the data analysis of the student interest in learning questionnaire, the ideal score is 92.89%, which is in the very good category. So, it can be concluded that the influence of using blog media on interest in learning the personal experience writing skills of class V students at SDN 179 Tanah Beru, Bulukumba Regency is in the very good category.